2017
DOI: 10.1093/nar/gkx260
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional approaches for optogenetic regulation of gene expression in mammalian cells using Arabidopsis cryptochrome 2

Abstract: Optogenetic tools allow regulation of cellular processes with light, which can be delivered with spatiotemporal resolution. In previous work, we used cryptochrome 2 (CRY2) and CIB1, Arabidopsis proteins that interact upon light illumination, to regulate transcription with light in yeast. While adopting this approach to regulate transcription in mammalian cells, we observed light-dependent redistribution and clearing of CRY2-tethered proteins within the nucleus. The nuclear clearing phenotype was dependent on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 39 publications
0
61
0
Order By: Relevance
“…Most light-inducible gene expression systems were established in yeast cells. Some light-inducible gene expression systems optimized in yeast cells do not work efficiently in mammalian cells (Pathak et al, 2017;unpublished data). Therefore, we conducted functional screenings of candi-date constructs in the immortalized human embryonic kidney cell line HEK293T (Figures 1, S1, and S2; Tables S1, S2, S3, S4, and S5).…”
Section: Functional Screening Of Optimized Pa-tet-off Transcription Fmentioning
confidence: 99%
See 3 more Smart Citations
“…Most light-inducible gene expression systems were established in yeast cells. Some light-inducible gene expression systems optimized in yeast cells do not work efficiently in mammalian cells (Pathak et al, 2017;unpublished data). Therefore, we conducted functional screenings of candi-date constructs in the immortalized human embryonic kidney cell line HEK293T (Figures 1, S1, and S2; Tables S1, S2, S3, S4, and S5).…”
Section: Functional Screening Of Optimized Pa-tet-off Transcription Fmentioning
confidence: 99%
“…However, we did not observe apparent light-induced gene expression in either case when CIB1 and its derivatives were fused to the N terminus or C terminus of p65 AD (Figures S1A-S1D; Tables S1 and S2). This may be due to the nuclear clearing phenotype of Cry2-tethered proteins (Pathak et al, 2017). When Cry2 is fused to certain nuclear-localized proteins having internal dimerization domains, the fused proteins are redistributed outside the nuclei in a lightdependent manner.…”
Section: Functional Screening Of Optimized Pa-tet-off Transcription Fmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that certain synthetic transcription factors fused to CRY2 exhibited a clusteringdependent slow nuclear clearance and consequently exhibited diminished TF activity upon blue light illumination. Bidirectional control over gene expression was achieved [171] by coupling this light-dependent transcriptional disruption to light-dependent degradation of its transcriptional target protein [172].…”
Section: The Release Of a Plasma Membrane-sequestered Transcription Fmentioning
confidence: 99%